Design of Submicroscopic Book and Improving of Students Learning Outcomes for Remedial Program in Class XI for Buffer Solution (Journal of Innovative Science Education, 2019)
This study aims to develop the submicroscopic book and improving of students learning outcomes for remedial programs. A remedial program is one of the lessons used to improve student understanding and learning outcomes. The results of a survey conducted by researchers at 10 SMA/ MA in Cirebon that the implementation of remedial program rarely carried out remedial teaching activities due to time constraints. This research used R & D method with 4-D model which consists of 4 stages, that were define, design, develop, and dessimination. The results of a small scale test that there was an inproving in students learning outcomes after participating in the remedial program, from 17.14% to 58.62%. The results of a large scale test were carried out in two classes with an increase in student learning outcomes from 12.50% to 71.43% and 17.50% to 78.79%. Students gave the positive responses for remedial learning used submicroscopic book. The response of students in the small-scale test was 78.02% (good) and the results of a large-scale test were 80.50% (good) and 81.17% (very good). The teachers also gave a positive response for use of the submicroscopic book and that was 86.67% (very good). The use of this submicroscopic book can be the one of solutions for implementing remedial teaching.